Performance of modified mortar containing epoxy - Abdul Latip, Arisya; Ali, Noorwirdawati; Abdul Hamid, Noor Azlina; Salleh, Norhafizah; Abdullah, Siti Radziah; Shahidan, Shahiron (2020)
Performance of FRP are highly depending on the adhesive used. FRP known to have high specific strength and specific stiffness, high durability against corrosion, light in weight, easy and quick installation therefore reduced manufacture time, great versatility and reduced maintenance. Despite all the the advantages possessed by FRP, there are actually several drawbacks which mainly causes by the epoxy resin. The organic binder are harmful towards humans, expensive and not applicable on wet surface. This study modified and elevated the binder materials by combining different percentage of mortar and epoxy. Compressive strength, density and water absorption of the specimen were tested and the optimum percentage were determined. Epoxy without harderner that were tested in this study is ranging from 0-5 % and composite cement consisted of 50% of Ground Granulated Blast Slag (GGBS) and 50% of Ordinary Portland Cement (OPC). From the experimental results, 3% of epoxy gives promising results as partial replacement of mortar.